Ou isto ou aquilo: implicações entre maternidade e militância para mulheres que militaram em oposição à ditadura militar no Brasil (1964-1985) - Jaiza Pollyanna Dias da Cruz (2013)
The history of a country or a people, can be written and told by different versions. There is this way of narrating or writing, a peculiarity that socially constructed through the spaces and micro and macro social relations: the hierarchy will be maintained or omitted, highlighting an official version, legitimated as truth. In Brazil, the period of the military dictatorship (1964- 1985) also presents certain obscuritas regarding the experiences of different social groups in this context exception. Regarding this historical moment, beyond the political, economic and social transformations in gender relations should be seen as an important marker. Women who campaigned in opposition to the regime, to break with traditional patterns of marriage, parenthood and family constitution favored new models and social settings that contributed to the integration of women into a new social order, diluting the boundaries between public life and private. This paper aims to understand the experience of motherhood that women campaigned during the military dictatorship in Brazil. There were four interviews with women who have been pregnant and had conceived or termination of pregnancy during the period of militancy during the semi-underground, underground, prison, exile and post-release. For the organization and interpretation of data, we construct narratives of individual phenomenological perspective that aimed to capture the lived experience of these women in order to understand more generally the social construction of female identity, with primary focus on motherhood. The results showed that the model of maternity assumed by militants, although living in extreme situation and presenting ambiguities, moved between continuity and rupture in some points being approximated to the traditional model prevailing in society at the time, and modified by other conditions resulting from path of militancy, as well as models in which conjugal motherhood happened. Despite experiencing a context in which death was a prominent risk, motherhood contributed to the preservation of their lives, not stopping, however, that these women, though pregnant, suffer physical torture, sexual and psychological, as well as threats both relation to the maintenance of pregnancy, regarding the whereabouts of their children near him. After entering the militancy, these women broke with his family ties and social risks assumed by: getting pregnant unmarried; being arrested and tortured pregnant; undergo abortions; having their births during the arrest, hiding, exile and post-release without medical pre and post partum; apartadas be without their babies and breastfeed them under the threat of no longer being able to have them in my arms. Such situations limits required capabilities and overcoming resistance against adverse conditions, especially in the post-prison moment of rebuilding their lives and social ties, combining motherhood, marital, widowhood, career and survival in a little amalgam experienced by middle-class women that historical period, extending the range of design possibilities for women until the present day, linking the gender dimensions of the generation. Understanding these experiences within transformations also becomes a contribution to the field of study surrounding the psychosocial aspects of memory specifically in relation to the construction of a historical memory of this period, in order that the experience of these women in the context of dictatorship mark peculiar shape the trajectory of their lives; dimension little known / disclosed relationships with socially guarding the transformations experienced gender by women of the younger generations.